A Child with severe Nephrolithiasis and Nephrocalcinosis - Bahrun D.; Alatas H.; I. G. N. Wila Wirya; Himawan S. (Paediatrica Indonesiana, 1982)
A case of severe nephrolithiasis with nephrocalcinosis ill a six years old child has been reported.The diagnosis of nephroNthiasis was made based on the radiological examination and laboratory findings.The cause of hypercalciuria in this case was still obscure. Necropsy finding revealed a terminal renal failure with severe nephrocalcinosis.The cause of terminal renal failure in this case was probably multiple renal stones due to prolonged hyperca!ciuria and severe nephrocalcinosis, complicated by chronic renal infection.